Sustainable segmentation for ecological personal hygiene products in the hard discount format - Herrera González, Daniel Antonio (Cuadernos de Administración, 2021)
At present, there is little scientific research on the sustainable consumption of personal hygiene products in countries like Colombia. Thus, this study sought to analyze buyers in the general category of personal hygiene products who visit hard-discount stores in their everyday practices and intention of a sustainable purchase in their choice of product in order to segment or group them for developing efficient marketing strategies. A quantitative approach with a descriptive correlational scope was employed to analyze the relationship between consumers’ environmental practices and their intention of purchasing personal hygiene products. During the analysis stage, hierarchical grouping coupled with a Principal Component Analysis (PCA) was used to project the segments in the dimensions found. The quantitative results yielded three large segments with different sociodemographic characteristics, practices, and intentions for each group. With this information, the companies that market these grooming products will be able to create and enhance their strategies to build loyalty and increase sales in new segments of sustainable consumers, generating the impact that the planet and society need.